The High-Temperature In Situ Synchrotron Study of the Structural-Phase Transformations in 3D-Printed Ti–6Al–4V and Ti–5Al–3Mo–V Titanium Alloys; Physics of Metals and Metallography; Vol. 125, iss. 9 - Lobova T. A. Tatjyana Anatoljevna; Panin A. V. Alexey Viktorovich; Perevalova O. B. Olga Borisovna; Syrtanov M. S. Maksim Sergeevich (2024, 2024)
Title screen